Correlation of radiological and histopathological findings in the diagnosis of benign bone tumors - Eriten, Berna; Menekşe, Serdar (The European Research Journal, 2025)
Objectives: Diagnosis of benign bone tumors is one of the diagnostic questions in the clinical practice which has an impact on the patient’s quality of life. The work aimed to define the radiographic and histologic complementary diagnosis for benign bone tumors. Methods: The present cross-sectional study included one hundred and forty-two patients with benign bone and soft tissue tumors referred to and followed up in the Adana Seyhan Hospital over a study period of 2010 to 2023. Patients were categorized based on the tumor type and radiological imaging was done through X-ray, Computed Tomography (CT), and Magnetic Resonance Imaging (MRI) scans. These results were then compared to histopathologic outcomes. Diagnostic indices such as the percentage accuracy, sensitivity, specificity, and positive and negative predictive values were estimated. Results: In the study, 43.7% of the tumors were cartilaginous. MRI had the highest diagnostic accuracy (sensitivity of 96.9%, specificity of 83.3%, P<0.05). X-ray showed sensitivity of 90.8% and specificity of 66.7%, while CT showed sensitivity of 92.3% and specificity of 58.3%. A strong correlation was observed between radiologic and histopathologic findings (r=0.87, P<0.001). Conclusions: Out of the histopathological features, there is a closely related association between the radiological and histopathological appearances in the diagnosis of benign bone tumors. Magnetic Resonance Imaging appears to be the only imaging modality with high accuracy of diagnosis. The concomitant interpretation of radiologic and histopathologic features allows for a considerable enhancement in diagnostic specificity.